The Photocatalytic Reduction of Hexavalent Chromium by Controllable Mesoporous Anatase TiO2 Nanoparticles - Vorrada Loryuenyong; Natnapin Jarunsak; Thirawich Chuangchai; Achanai Buasri (Advances in Materials Science and Engineering)
Titania (TiO2) nanoparticles with periodical mesopore size (up to 150 Å) have successfully been synthesized by sol-gel template method, using titanium(IV) tetraisopropoxide as a starting precursor and isopropanol as a solvent. Different quantities of activated carbon (0%, 5%, and 10% by weight) were used as templates to control the porosity and particle size of titania nanoparticles. The templates were completely removed during the calcination in air at 500°C for 3 hr. The results showed that the specific surface area of titania is increased with increasing activated carbon content. The optical bandgap of synthesized titania exhibits a blue shift by 0.3–0.6 eV when compared to the reported value for the bulk anatase and rutile phases. The photocatalytic activity of porous titania is determined with its reduction efficiency of hexavalent chromium (Cr6+). The reduction efficiency is optimized under ultraviolet illumination.